Anti-heart and anti-intercalated disk autoantibodies: evidence for autoimmunity in idiopathic recurrent acute pericarditis. Issue 10 (6th May 2010) - Caforio, A L P; Brucato, A; Doria, A; Brambilla, G; Angelini, A; Ghirardello, A; Bottaro, S; Tona, F; Betterle, C; Daliento, L; Thiene, G; Iliceto, S
Abstract : Background: Idiopathic recurrent acute pericarditis (IRAP) is a rare disease of suspected, yet unproved, immune-mediated origin. The finding of serum heart-specific autoantibodies in IRAP would strengthen the autoimmune hypothesis and provide aetiology-specific non-invasive biomarkers. Objective: To assess frequency of serum anti-heart (AHA), anti-intercalated-disk (AIDA) and non-cardiac-specific autoantibodies and their clinical and instrumental correlates in patients with IRAP. Patients: 40 consecutive patients with IRAP, 25 male, aged 37±16 years, representing a large single-centre cohort collected at a referral centre over a long time period (median 5 years, range 1–22 years). Control groups included patients with non-inflammatory cardiac disease (NICD) (n=160), ischaemic heart failure (n=141) and normal subjects (n=270). Methods: AHA (organ-specific, cross-reactive 1 and 2 types) and AIDA were detected in serum samples from patients, at last follow-up, and control subjects by indirect immunofluorescence (IIF) on human myocardium and skeletal muscle. Non-cardiac-specific autoantibodies were detected by IIF, and anti-Ro/SSA, anti-La/SSB by ELISA. Results: The frequencies of cross-reactive 1 AHA and of AIDA were higher (50%; 25%) in IRAP than in NICD (4%; 4%), ischaemic (1%; 2%) or normal subjects (3%; 0%) (p=0.0001). AHA and/or AIDA were found in 67.5% patients with IRAP. Of the non-cardiac-specific antibodies, only antinuclear autoantibodies at titre ≥1/160 were more common in IRAP (5%) versus normal (0.5%, p<0.04). AIDA in IRAP were associated with a higher number of recurrences (p=0.01) and hospitalisations (p=0.0001), high titre (1/80 or higher) AHA with a higher number of recurrences (p=0.02). Conclusions: The detection of AHA and of AIDA supports the involvement of autoimmunity in the majority of patients with IRAP.